Efek Ekstrak Etanol Rimpang Temu Mangga (Curcuma mangga Val.) Terhadap Sel β Pankreas Mencit Putih Yang Diinduksi Aloksan Secara Histologis - Ridho Hendrikos; Netty Marusin; Djong Hon Tjong (Jurnal Biologi Universitas Andalas, 2014)
The effect of mango ginger (Curcuma mangga Val.) ethanolic extract has been experimentally tested to β cell of alloxan-induced mice at the Laboratory Animal Development and Structure. The experiment aimed to identify the effectifity of the ethanolic extract to defend β cell from necrosis caused by the alloxan. The activity of the extract was evaluated by using control (A0 and A1) and treatments. All mice were induced by alloxan (150 mg/kg of body weight). One week later the extract was given orally to the mice at dose 200 (A2) 400 (A3) and 800 (A4) mg/kg of body weight (A4). The extract was given everyday for 21 days. Pancreas were isolated for each week. The observation of pancreas histology showed that extract 200 mg/kg body weight could decrease necrosis at Langerhans higher than the extract of 400 and 800 mg/kg of body weight. This results indicate that giving mango ginger extract at dose 200 mg/kg body weight could decrease β cell necrosis.Key words : mango ginger (Curcuma mangga Val.), β cell, alloxan, necrosis.